Psychosocial care of immigrants in the Czech Republic as a country in transition - Duchonova, Katerina (The British journal of psychiatry, 2020)
The Czech Republic is a country in transition, and its historical sociopolitical isolationism lingers to this day, with restrictive attitudes towards immigrants. International collaborations among transcultural psychiatrists and non-governmental organisations (NGOs) could help increase awareness of the service needs of immigrants and improve access to mental healthcare. A lack of state and academic interest persists despite the increasing importance of the issue. These neglected problems burden NGOs that have limited financial and staffing resources. Legislation on the humanitarian needs of immigrants must enhance the efforts of NGOs, and psychiatrists may serve as liaisons to effect the necessary change.
Keywords: psychosocial interventions; emigranti a imigranti; psychiatrická rehabilitace; Humans; Psychiatric Rehabilitation; human rights; Organizations; psychiatrie; Emigrants and Immigrants; organizace; lidé; Delivery of Health Care; poskytování zdravotní péče; Czech Republic; Mental Health Services; Psychiatry; služby péče o duševní zdraví; immigration policy; Česká republika; Transcultural psychiatry; stigma and discrimination